2004
DOI: 10.1523/jneurosci.3340-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

A New Rat Model of the Human Serial Reaction Time Task: Contrasting Effects of Caudate and Hippocampal Lesions

Abstract: There is often little correspondence between human and animal examples of nondeclarative memory. The serial reaction time task (SRT) is a sequence learning example of human nondeclarative memory that may be suitable for development as an animal model. The SRT is believed to be impaired by basal ganglia, not limbic system damage, but there is uncertainty whether limbic system pathology does in fact leave the SRT unimpaired. We therefore developed a new rat model that closely approximated the human SRT, using in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
2
33
1
Order By: Relevance
“…Graybiel (1998) proposed that the basal ganglia contribute to S-R learning by chunking representations of action sequences. Consistent with this, Christie and Dalrymple-Alford (2004) report that dorsal striatal lesions spare serial reaction time learning for sequences of four nose pokes but not for longer sequences of 8 or 12 nose pokes. The ability to learn the shorter sequence is in agreement with evidence in the present study that CPu and mCPu lesions spare basic aspects of habit learning.…”
Section: Effects Of Striatal Lesions On Serial Reaction Time Learningsupporting
confidence: 65%
See 3 more Smart Citations
“…Graybiel (1998) proposed that the basal ganglia contribute to S-R learning by chunking representations of action sequences. Consistent with this, Christie and Dalrymple-Alford (2004) report that dorsal striatal lesions spare serial reaction time learning for sequences of four nose pokes but not for longer sequences of 8 or 12 nose pokes. The ability to learn the shorter sequence is in agreement with evidence in the present study that CPu and mCPu lesions spare basic aspects of habit learning.…”
Section: Effects Of Striatal Lesions On Serial Reaction Time Learningsupporting
confidence: 65%
“…Recording studies in nonhuman primates have shown changes in neural activity in striatum that correspond to visuomotor sequence learning, an involvement confirmed by behavioral impairments observed when striatum is reversibly inactivated (Miyachi et al, 1997(Miyachi et al, , 2002. Caudate-putamen lesions in rats have been found to disrupt serial reaction time learning measured by interference effects, increases in RT observed when subjects trained with a repeating sequence are switched to random sequences (Christie and Dalrymple-Alford, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite the enormous amount of work that has been devoted to characterizing the neurophysiological and motor phenotypes of these mice, there is limited information about their cognitive phenotypes, and no procedures have been developed to help determine how nondeclarative learning might be compromised by any developing neurodegenerative phenotype. A rodent analog of the SRT was recently developed in rats (Christie and Dalrymple-Alford 2004). Neurologically intact rats demonstrated an ability to learn short (4-trial), medium (8-trial) length sequences, and long (12-trial) sequences.…”
mentioning
confidence: 99%